Electromagnetic Interference Shielding and Physical-Mechanical Characteristics of Rubber Composites Filled with Manganese-Zinc Ferrite and Carbon Black - Kruželák, Ján; Kvasničáková, Andrea; Hložeková, Klaudia; Dosoudil, Rastislav; Gořalík, Marek; Hudec, Ivan (Polymers, 2021)
In the present work, composite materials were prepared by incorporation of manganese-zinc ferrite, carbon black and combination of ferrite and carbon black into acrylonitrile-butadiene rubber (NBR). For cross-linking of composites, standard sulfur-based curing system was applied. The main goal was to investigate the influence of the fillers on the physical-mechanical properties of composites. Then, the electromagnetic absorption shielding ability was investigated in the frequency range 1 MHz-3 GHz. The results revealed that composites filled with ferrite provide sufficient absorption shielding performance in the tested frequency range. On the other hand, ferrite behaves as an inactive filler and deteriorates the physical-mechanical characteristics of composites. Carbon black reinforces the rubber matrix and contributes to the improvement of physical-mechanical properties. However, composites filled with carbon black are not able to absorb electromagnetic radiation in the given frequency range. Finally, the combination of carbon black and ferrite resulted in the modification of both physical-mechanical characteristics and absorption shielding ability of hybrid composites.
Keywords: physical-mechanical properties; ferrite; absorption shielding; electromagnetic interference; carbon black